2018
DOI: 10.1525/elementa.277
|View full text |Cite
|
Sign up to set email alerts
|

Ocean dinitrogen fixation and its potential effects on ocean primary production in Earth system model simulations of anthropogenic warming

Abstract: Dinitrogen fixation (DNF) provides a large fraction of the 'new' nitrogen supporting upper ocean productivity, and is associated with environmental conditions likely to show substantial change under anthropogenic warming. For example, surface warming induces stronger stratification, weaker nutrient supply and more rapid nutrient depletion. Using six Earth System Models, we have examined spatial patterns and trends of DNF in the CMIP5 historical and RCP 8.5 experiments. Four models (CanESM2, CESM1-BGC, IPSL-CM5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…N 2 fixation in IPSL‐CM5A‐LR was scaled to balance denitrification, which may have been overestimated (Séférian et al, ). We therefore rescaled N 2 fixation in IPSL‐CM5A‐LR by 0.17 following Riche & Christian, . In our comparisons, we included models obtained from four additional studies: (1) Luo et al () derived estimates of global N 2 fixation based on a stepwise MLR between observed N 2 fixation rates and predictors; (2) Landolfi et al () combined resource competition theory and a coupled ecosystem‐circulation model to explain the high N 2 fixation rates in nitrogen‐rich waters of the North Atlantic but also provided a model for the global ocean; (3) Jickells et al () evaluated the effects of atmospheric nitrogen deposition on marine N 2 fixation using the output from the PlankTOM model (Buitenhuis et al, ; Le Quéré et al, ); Finally, (4) Paulsen et al () incorporated a prognostic representation of diazotrophs in MPI‐ESM to map marine N 2 fixation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…N 2 fixation in IPSL‐CM5A‐LR was scaled to balance denitrification, which may have been overestimated (Séférian et al, ). We therefore rescaled N 2 fixation in IPSL‐CM5A‐LR by 0.17 following Riche & Christian, . In our comparisons, we included models obtained from four additional studies: (1) Luo et al () derived estimates of global N 2 fixation based on a stepwise MLR between observed N 2 fixation rates and predictors; (2) Landolfi et al () combined resource competition theory and a coupled ecosystem‐circulation model to explain the high N 2 fixation rates in nitrogen‐rich waters of the North Atlantic but also provided a model for the global ocean; (3) Jickells et al () evaluated the effects of atmospheric nitrogen deposition on marine N 2 fixation using the output from the PlankTOM model (Buitenhuis et al, ; Le Quéré et al, ); Finally, (4) Paulsen et al () incorporated a prognostic representation of diazotrophs in MPI‐ESM to map marine N 2 fixation.…”
Section: Methodsmentioning
confidence: 99%
“…N 2 fixation in IPSL-CM5A-LR was scaled to balance denitrification, which may have been overestimated (Séférian et al, 2013). We therefore rescaled N 2 fixation in IPSL-CM5A-LR by 0.17 following Riche & Christian, 2018. In our comparisons, we included models obtained from four additional studies: (1) Luo et al (2014) derived estimates of global N 2 fixation based on a stepwise MLR between observed N 2 fixation rates and predictors; (2) Landolfi et al (2015) combined resource competition theory and a coupled ecosystem-circulation model to explain the high N 2 fixation rates in nitrogen-rich waters of the North Atlantic but also provided a model for the global ocean;…”
Section: Outputs Of N 2 Fixation From Other Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of carbon by the oceans affects marine chemistry via ocean acidification (Gattuso and Buddemeier, 2000;Orr et al, 2005;Doney et al, 2009), a process that increases seawater concentrations of CO 2 , H + , and HCO − 3 and reduces pH and CO 2− 3 ion concentrations. The oceans have absorbed approximately 30 % of anthropogenic carbon emissions since the pre-industrial era (Sabine et al, 2004;Khatiwala et al, 2009Khatiwala et al, , 2013Gruber et al, 2019), resulting in global surface pH declines of approximately 0.1 units (Bindoff et al, 2007). Declines in global open ocean surface pH are 0.018 units per decade over 1991-2011 (Lauvset et al 2015), with individual time series stations exhibiting declines of 0.017 to 0.027 units per decade (Bindoff, et al, in press).…”
mentioning
confidence: 99%
“…In the coming decades, the oligotrophic subtropical biomes are predicted to expand poleward as a result of global warming (Polovina, Dunne, Woodworth, & Howell, 2011), while the effect of environmental change on the diazotrophic activity is still in debate owing to the complex response to shift of limiting nutrients (phosphate and iron) supply and increase of CO 2 concentration (Eichner, Rost, & Kranz, 2014;Riche & Christian, 2018). Nevertheless, the outlined changes in subtropical waters may affect the diazotroph community composition in the future ocean because the nutrient requirement and the response to enriched CO 2 conditions differ among diazotrophic species (Eichner et al, 2014;Riche & Christian, 2018). As mentioned above, the transfer pathway of the biologically fixed nitrogen in the grazing food chain differs depending on the diazotroph species (Bonnet, Baklouti, Gimenez, Berthelot, & Berman-Frank, 2016).…”
Section: Geographical Pattern Of the Diazotrophic Contribution Of Nmentioning
confidence: 99%